PEMANFAATAN TPACK DALAM MENINGKATKAN LITERASI NUMERASI DAN KESEHATAN DI DESA KACARIBU - Sitorus, Nurhayati; Jonson, Jonson Jusufri Pasaribu; Ginting, Audy Christie Putri; Tambunan, Verawaty Angelia (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2024)
Numeracy literacy is knowledge and skills in using various kinds of numbers and symbols related to mathematics as a basis for solving practical problems in everyday life and analyzing information in various forms such as graphs, tables, charts and so on. The aim of this service activity will be achieved by providing a learning platform such as afternoon tutoring which will guide and create a fun learning atmosphere for TPACK, for the Health section by providing assistance, training and guidance to village residents to introduce good practices in increasing mutual cooperation motivation. and Health sections such as posyandu. In fact, from the results of an interview with the village head, Mr. Andreas Purba, the literacy and numeracy level of students in Kacaribu village, Kabanjahe sub-district is still relatively low due to the low interest in learning of students which is caused by monotonous learning without linking it to technological developments, thereby reducing participants' interest in learning. grew up in the village. Therefore, the PKM team in Kacaribu village offers a solution for using TPACK to improve literacy and numeracy, where TPACK is a learning method that applies technology in the learning process, such as using Canva, PPT and other media as tools in learning. Not only in terms of literacy and numeracy, but health also plays an important role in creating an active and creative educational environment. Health does not only involve nutrition entering students' bodies, but the environment also has a big influence on health. Because if the community environment is clean and healthy then this can improve the quality of education, but if the community environment is dirty it can support the scope of education where students will breathe dirty air which will affect the comfort of learning. This service uses a participatory action service design (Action Research) with a qualitative approach. This design was chosen because the aim of this service is to help the community, especially students in Kacaribu village, in improving numeracy literacy and health, so active participation is needed from the Kacaribu village community to achieve this goal. With the assistance activities of Kacaribu Village residents to practice using TPACK to improve literacy, numeracy and health, there was a significant increase in students' interest in learning in taking additional lessons held at the Kacaribu Village office and also the enthusiasm of students in using TPACK in the learning process at Kabanjahe 2 Catholic High School. The community service program also shows that the program implemented has a positive impact on increasing knowledge and awareness of the Kacaribu Village community in increasing awareness of health at posyandu. It also shows that community awareness of health can be influenced by certain factors. In this case, the mentoring program implemented was successful in increasing community knowledge in improving awareness and health.